Kebijakan Sekaya Maritim dalam Rangka Peningkatan Kesejahteraan Nelayan di Lampung Timur: Analisis Tantangan dan Peluang - Rachma Indriyani; Ayub Torry Satriyo; Diah Apriani Atika Sari (Faculty of Law, Maranatha Christian University, 2015)
Fishing has been a traditional occupation for millennia, supporting a plethora of communities, both along the sea coast and inland. However, traditional fishermen are under pressure from large scale unregulated industrialization, export-oriented, mechanized fishing and aquaculture. Therefore, it’s community faced with deprivations of many kinds. The Ministry of Marine Affairs and Fisheries has been launching Sekaya Maritim program since early 2015, as an effort to improve the welfare of traditional fishermen. Considering that every region has different culture and problems to each other, then it should be a policy which appropriated to the real needs of local fishing communities. Nevertheless, one fits for all could not always fix all. Through descriptive approach and case study analysis, this paper reviews the Sekaya Maritim program applied in East Lampung, as well as map out the challenges and opportunities that should be a reflective matter for the government, so that the program could be optimally implemented and precisely targeted.